Manajemen Barang Milik daerah dan Optimalisasi Pengelolaan Aset Provinsi X - Periansya, Periansya; Sari, Yuliana; Azmi, Farah (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p13, 2022)
This study aims to determine the relationship between regional property management to the optimization of asset management as well as planning, identification of BMD, BMD inventory and supervision and control as a variable. Data were collected from employees of the regional financial and asset management agency of South Sumatra Province through a structured questionnaire. The sample used was 56 employees at the Regional Financial and Asset Management Agency of South Sumatra Province and analyzed using SPSS version 25. The results showed that the Planning and Supervision and Control variables had a significant positive effect on the optimization of asset management, while the BMD Identification variable had a negative effect. Inventory BMD does not affect the optimization of asset management. Keywords: Planning; Identification; Inventory; Supervision and Control; Optimization of Asset Management